Особистість в освітньому середовищі, яке динамічно трансформується - Олексенко, Роман Іванович; Олексенко, Роман Иванович; Oleksenko, Roman; Васюк, Ю. В. (My University, 2017)
UK: У статті на засадах культурофілософського аналізу феномену особистості в соціокультурному просторі нинішнього суспільства, яке динамічно трансформується, та з позицій розгляду специфіки трансформаційних процесів в українському освітньому середовищі проведено виокремлення чинників самовизначеності особистості у контексті порівняння з епохами, співзвучними до сучасності. EN: The article is based on analysis of the phenomenon culturalityphilosophy individual educational space in this society that rapidly transformed, and from the standpoint consideration the specific transformation processes in Ukrainian educational environment conducted search samovyznachenosti social factors in thecontext of the individual compared with the age, similar to the present. The ambiguity of the current situation in Ukraine led to identify common trends in past eras, in particular – the era of Modernism late nineteenth – early twentieth century. The problem of finding ways harmonious development of human personality with complex socio-cultural transformation processes of transformation of society in the critical period of its existence. It was always important to understand how social factors (collective community of people) contrary to or blended with personal principle (individual for each person). The purpose of scientific exploration elected summarizing trends philosophical understanding of the formation and development of personality, consideration of socio-cultural factors influence its existence to the development of individual qualities important in the context of comparing eras, in tune with modern times. Analyzed the works of famous philosophers and teachers of the past (J. Gibson, R. Steiner, N. Berdyaev, K. Ushinsky) scientists today (S. Goncharenko, O. Marchenko, R. Oleksenko V. Slobodchikov) who discovered the concepts of analysis «personality», «medium», «educational environment». A comparative analysis of public art nouveau and modern information society in relation to social and cultural factors in the circumstances of self-identity transformations educational environment.
Personality in an educational environment that dynamically transforms
Keywords: особистість; суспільні трансформації; освітнє середовище; епоха модерну; personality; social transformation; educational environment; the era of modernism